An interview study exploring Tesla drivers' behavioural adaptation. (October 2018) - Lin, Rui; Ma, Liang; Zhang, Wei
Abstract: Partially automated vehicles (PAVs) have been used in real-world environments for several years since the emergence of autonomous driving. It is important to understand the effects of partial automation systems (PAS) on the understanding of drivers and their behaviour during the first months of use. In order to adapt to new vehicle technology, drivers usually exhibit specific behaviours in this stage that are not intended by the developers, namely behavioural adaptation. The present study investigated the behavioural adaptations by early PAV adopters after short-term usage. A semi-structured interview was conducted among 20 Tesla drivers who had relatively high experience (one to five months) with Autopilot, and the interviews were synthesized to understand their behavioural adaptation, mental models, and trust during the period of use. The results showed that PAV drivers had a very positive attitude towards the PAS and drivers universally engaged in secondary tasks during automated driving. They also learned from their experiences to identify relatively safe usage conditions and they employed a safety margin to avoid exposure to excessively risky situations. Highlights: Tesla drivers rely mainly on trial-and-error to learn automatic system functions. Engagement in secondary tasks during partially automated driving was universal. Self-regulatory countermeasures are used to maintain safety while engaging secondary tasks.